2021
DOI: 10.3390/met11081198
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of LSP on the Structure Evolution and Self-Heating of ARMCO Iron under Cyclic Loading

Abstract: This work is devoted to the experimental investigation of the effect of laser shock peening (LSP) on the thermo-mechanical properties of metals. ARMCO iron was chosen as the model material for the study. Samples were subjected to LSP, and were tested following the procedure of the self-heating (Risitano) technique. To investigate the damage that was induced by heating, the fatigue tests were coupled with infrared thermography measurements. The results of the study showed that the LSP procedure qualitatively ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Based on satisfying the strength of the titanium alloy, reducing the temperature of diffusion bonding of titanium alloy will significantly improve the production efficiency of diffusion bonding of the titanium alloy. Due to more grain boundaries, nanomaterials provide more short-range diffusion channels for atomic diffusion, which can significantly improve the diffusion ability of atoms at the interface and inside the material [19][20][21][22][23][24][25]. At present, studies have shown that better diffusion joints can be obtained by shot peening of titanium alloy [26,27], stainless steel [28], and other metals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on satisfying the strength of the titanium alloy, reducing the temperature of diffusion bonding of titanium alloy will significantly improve the production efficiency of diffusion bonding of the titanium alloy. Due to more grain boundaries, nanomaterials provide more short-range diffusion channels for atomic diffusion, which can significantly improve the diffusion ability of atoms at the interface and inside the material [19][20][21][22][23][24][25]. At present, studies have shown that better diffusion joints can be obtained by shot peening of titanium alloy [26,27], stainless steel [28], and other metals.…”
Section: Methodsmentioning
confidence: 99%
“…Due to more grain boundaries, nanomaterials provide more short-range diffusion channels for atomic diffusion, which can significantly improve the diffusion ability of atoms at the interface and inside the material [19][20][21][22][23][24][25]. At present, studies have shown that better diffusion joints can be obtained by shot peening of titanium alloy [26,27], stainless steel [28], and other metals.…”
Section: Introductionmentioning
confidence: 99%